2017
DOI: 10.1016/j.ejvs.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Asymmetric and Symmetric Dimethylarginine Levels after Iloprost Treatment in Patients with Buerger's Disease

Abstract: Iloprost treatment decreases ADMA and SDMA, which are associated with endothelial dysfunctions in patients with Buerger's disease. Of note, the still higher than normal range of SDMA levels after iloprost treatment suggests that treatment should continue until SDMA levels are within the normal range in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In addition, ADMA inhibits NO and Şenol Iloprost and ADMA Levels 109 reduces vascular compliance, increase vascular resistance, and limit blood flow (7). It is shown that angiogenic growth factors stimulate NO release (24) and require NO in order to perform angiogenic functions (17,25,26). Jacobi et al (27) have demonstrated that the inhibition of ADMA has increased angioadaptation against ischemic and inflammatory stimulants in mice and angiogenesis and arteriogenesis has recovered.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ADMA inhibits NO and Şenol Iloprost and ADMA Levels 109 reduces vascular compliance, increase vascular resistance, and limit blood flow (7). It is shown that angiogenic growth factors stimulate NO release (24) and require NO in order to perform angiogenic functions (17,25,26). Jacobi et al (27) have demonstrated that the inhibition of ADMA has increased angioadaptation against ischemic and inflammatory stimulants in mice and angiogenesis and arteriogenesis has recovered.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are studies being conducted to evaluate the efficacy of new drugs and certain procedures dependent on disease staging; surgical sympathectomies, mononuclear cell therapy, iloprost, etc. [5-7]. Despite these promising studies, for now, we are only able to offer our patients information and means of smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we do not have comprehensive data on pre-screening medication, food intake or staging information of the participants for the study. Certain medications can affect the blood levels of distinct metabolites, as observed for ADMA and SDMA in patients [80]. Notably, the control population of the training cohort was somewhat younger.…”
Section: Limitations Of the Studymentioning
confidence: 95%